The Effect of the CIRC (Cooperative Integrated Reading and Composition) Model on Student Learning Outcomes Theme 6 Class III SDN 106158 Pematang Johar - Robenhart Tamba; Tetny Tessalonika Naibaho; Tri Wahyu Purnomo (Indonesian Journal of Advanced Research, 2023)
The purpose of this study was to find out how the effect of learning using the CIRC (Cooperative Integrated Reading and Composition) model on student learning outcomes in class III theme 6 SDN 106158 Pematang Johar. This research is a quantitative study with a quasi-experimental methodology (Quasi Experimental Design). The design used was the Pretest-Posttest Control Group Design. The subjects in this study were 20 students in class III A and 24 students in class III B. Data collection techniques in this study used tests, observation, documentation and interviews. This study uses quantitative data analysis techniques. Data on student learning outcomes were collected using the theme 6 learning outcomes test which was given using the CIRC (Cooperative Integrated Reading and Composition) learning model and using conventional. Data analysis using descriptive and inferential analysis techniques. The study results showed that the posttest average score of student learning outcomes using the CIRC (Cooperative Integrated Reading and Composition) model was 83.40 and that of the control class was 72.50. Based on the t-test conducted on the experimental class posttest and control class posttest values, a t_count of 3.6340 and t_(table) 2.0810 is obtained at a significance level of 0.05. The t_table value can be seen in the attachment. Because t_count > t_table is 3.6340 > 2.0810 then Ho is rejected and Ha is accepted which states that there is an influence of the CIRC (Cooperative Integrated Reading and Composition) learning model on student learning outcomes in theme 6 sub-theme 4 learning 4 class III SDN 106158 Pematang Johar.